Anterior Cruciate Ligament Reconstruction with LARS Artificial Ligament—Clinical Results after a Long-Term Follow-Up - Parchi, Paolo Domenico; Ciapini, Gianluca; Paglialunga, Carlo; Giuntoli, Michele; Picece, Carmine; Chiellini, Fabio; Lisanti, Michele; Scaglione, Michelangelo (Joints, 2018)
Purpose The aim of this retrospective study was to evaluate the subjective and functional outcome of anterior cruciate ligament (ACL) reconstruction with the synthetic Ligament Advanced Reinforcement System (LARS) ligament.Methods Twenty-six patients were reviewed at an average follow-up of 11.6 years. Objective clinical evaluation was performed with stability tests. Patient-reported outcomes (Visual Analogue Scale, Knee Injury and Osteoarthritis Outcome Score, and Cincinnati Knee Rating Scale) were used to assess subjective and functional outcomes.Results Overall satisfactory results were obtained in 22 cases (84.6%). Four patients (15.4%) showed mechanical failure of the graft. No cases of synovitis or infection were reported.Conclusion LARS ligament can be considered a safe and suitable option for ACL reconstruction in carefully selected cases, especially elderly patients needing a rapid postoperative recovery.Level of Evidence Level IV, retrospective case series.
Keywords: anterior cruciate ligament; reconstruction; ligament reinforcement; artificial ligament; LARS ligament